(untitled) (Bangladesh Journal of Animal Science, 2019)
The aim of the experiment was to investigate the productive and reproductive potential of pregnant Red Chittagong (RC) cows through improved feeding. A total of 30 pregnant RC cows from each of 30 farmers having six months pregnancy and between 2 and 3 parities old were used in the trial. The cows were randomly allocated to three dietary treatment groups, i.e., T0, T1 and T2. The cows of T0 group received farmers’ diet (63% of dry matter intake of cows according to ARC, 1995) without the supplementation and served as control. The cows of T1 group received farmer’s diet (63%) plus 25% supplementation of formulated concentrate diet for deficit of requirement of cows (63 + 9.25) = 72.25% dry matter intake of cows according to ARC, 1995) and T2 group received farmers diet (63%) plus formulated concentrate diet to meet 100% requirements of cows according to ARC (1995) (63% +37%) = 100%. The total live weight gain before calving of RC cows were observed significantly (P <0.05) higher in T2 and T1 groups than T0 group. The calves birth weight was found significantly (P <0.05) higher in T2group than T1 and T0 groups. The gestation length was increased approximately 3 and 2 days for T2 and T1 groups, respectively, compared to T0 group. Therefore, the farmer’s diet plus supplementation of formulated concentrate diet to meet 100% requirement of cows according to ARC (1995) (63% +37%) = 100% was a better improved feeding system of pregnant Red Chittagong cows. Bang. J. Anim. Sci. 2019. 48 (1):42-47